Downstream Regulatory Element Antagonist Modulator Regulates Ca(2+) Homeostasis and Viability in Cerebellar Neurons - Gomez-Villafuertes, Rosa (J Neurosci, 2005)
The Na(+)/Ca(2+) exchangers NCX1, NCX2, and NCX3 are vital for the control of cellular Ca(2+) homeostasis. Here, we show that a doublet of downstream regulatory element sites in the promoter of the NCX3 gene mediates transcriptional repression of NCX3 by the Ca(2+)-modulated transcriptional repressor downstream regulatory element antagonist modulator (DREAM). Overexpression of a DREAM EF-hand mutant insensitive to Ca(2+) (EFmDREAM) in hippocampus and cerebellum of transgenic mice significantly reduced NCX3 mRNA and protein levels without modifying NCX1 and NCX2 expression. Cerebellar granules from EFmDREAM transgenic mice showed increased levels of cytosolic Ca(2+) and were more vulnerable to increased Ca(2+) influx after partial opening of voltage-gated plasma membrane Ca(2+) channels induced by increasing K(+) in the culture medium but survived better in the conditions of reduced Ca(2+) influx prevailing in low extracellular K(+). Overexpression of NCX3 in EFmDREAM transgenic granules using a lentiviral vector restored the normal survival response to high K(+) observed in wild-type granules. Thus, the downregulation of the regulator of Ca(2+) homeostasis NCX3 by Ca(2+)-regulated DREAM is a striking example of the autoregulatory property of the Ca(2+) signal in neurons.